Investigation of mechanical properties of microwave welded SS304-SS202 lap joints. (1st February 2023) - Samyal, Rahul; Bedi, Raman; Bagha, Ashok Kumar
Abstract: The joint between dissimilar materials is always challenging to develop through traditional techniques due to the different properties of the parent materials. However, a novel non-traditional route of joining similar and dissimilar materials through energy conversion and absorption has been developed called SMHH (selective microwave hybrid heating). It has gained much attention due to its unique heating abilities. In the present work, the lap joint between SS202-SS304 is developed through SMHH placing nickel powder as an interlayer. The lap joint was characterized mechanically through shear tests and microhardness. Since the sheared area of the joint is large, it is challenging to achieve a good joint. Thus, to develop a solid joint, laser surface texturing (LST) was introduced to the joining surfaces, and the joints were characterized. After LST was introduced, a fully diffused joint interlayer region was observed through scanning electron microscopy (SEM). The EDS results confirmed the complete metallurgical bonding occurred by the diffusion of elements across the weld zone. From the XRD spectrum, the formation of intermetallic compounds like FeNi, FeNi3, C3 Fe7, and M23 C6 were identified at the joint region. The mean microhardness of 355 ± 10 HV was determined at the joint region of lap joints with LST. A lap joint with LST exhibits 217 MPa of shear strength, which is significantly higher than the joints without LST. Fractography of the shear failure specimens pointed out that partial heating of the interlayer caused incomplete bonding of the base metal and interlayer for without LST lap joints. However, mixed mode failure of SS202 near the overlap region of the LST lap joint occurred. It is concluded that the addition of LST on the lap joint has made a colossal impact on enhancing joint strength and intermetallic bonding. In addition, temperature-time profiling was studied to understand the heating mechanism involved in SMHH using thermocouples.